Perbandingan Jumlah Leukosit Darah Pada Pasien Appendisitis Akut Dengan Appendisitis Perforasi - Wahyu Wijaya; Mizar Eranto; Ringgo Alfarisi (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Appendicitis or inflammation of the appendicitis is one of the mortality rates of 0.2 - 0.8% in the world, in Indonesia itself appendicitis ranks fourth most inpatients. Appendicitis is one of the causes of abdominal emergencies in developing countries, cases of appendicitis occur more in males than females by a ratio of 1: 4, and strike at an average age of 10 to 30 years. Research purposes: Knowing the comparison of the number of leukocytes between patients with acute appendicitis and perforated appendicitis in RSUD H. Dr. Abdul Moeloek in 2017-2019. Research methods: This type of research is quantitative with observational analytic research design with a snowball approach. Retrieval of data using secondary data by looking at the number of leukocytes in the respondent's medical record. Bivariate analysis with Independent T-test. Results: The number of respondents 56 people known univariate test the number of leukocytes Acute Appendicitis as many as 28 people and Perforated Appendicitis as many as 28 people. Bivariate test results obtained p-value = 0,000. Conclusion: Available significant difference in the number of leukocytes Acute Appendicitis group with Perforated Appendicitis.